E-012 Outcomes following thrombectomy in cerebral venous sinus thrombosis: a propensity matched analysis of the national inpatient sample from 2016–2019. (23rd July 2022) - Hardigan, T; Siddiqui, N; Hardigan, A; Yaeger, K; Kellner, C; de Leacy, R; Fifi, J; Mocco, J; Majidi, S
Abstract : Introduction/Purpose: Cerebral venous sinus thrombosis (CVST) is a relatively uncommon but significant cause of cerebrovascular injury that can lead to severe morbidity and mortality. The primary aims of this study were to investigate the use of thrombectomy in CVST on rates of mortality and to determine factors predictive of good outcomes. Methods: A query of the 2016–2019 National Inpatient Sample was performed for patients admitted with ICD-10 diagnosis codes (I636, G08, I676, O225, O873) for CVST. The rate of endovascular thrombectomy was identified using ICD-10 codes (03CG, 03CK3, 03CL3, 03CP, 03CQ3, 037K3, 037L3, 037P3, 037Q3, 05CL3ZZ). Demographics, baseline comorbid conditions, and indicators of disease severity (defined as presence of seizure, ICH, SAH, coma and hydrocephalus) were compared between the patients who underwent endovascular thrombectomy and those who were medically managed. The rates of in-hospital mortality and discharge to home/acute-rehabilitation-facility (good outcome) were identified in each group. Propensity score matching was utilized to control for all significantly different potential baseline confounders such as age, race, gender, smoking, atrial fibrillation, hypertension, hyperlipidemia, diabetes, and indicators of disease severity. A multivariate logistic regression was performed to determine predictors of good outcome while controlling for comorbidity covariates and disease severity. Odds ratios were calculated for each respective predictor. Statistical significance was set at an alpha level of 0.05. All statistical analysis performed using R version 4.1.3. Results: A total of 103, 464 patients with CVST were identified from 2016–2019. Of those, 1, 035 patients (1.0%) underwent endovascular thrombectomy. Average age in the thrombectomy group was significantly lower (46.92±18.62 years vs. 58.99±19.31 years, p<0.001), with a higher percentage of women (59.9% vs. 51.93%, p<0.05). Patients in the thrombectomy group were more likely to be diagnosed with coma (24.19% vs. 4.37%), ICH (42.03% vs. 4.15%), seizure (25.12% vs. 8.14%), SAH (22.71% vs. 1.97%), and hydrocephalus (8.21% vs. 1.64%) (p<0.001 for all). Non-thrombectomy patients were older and had higher rates of hypertension (62.1% vs. 43.48%), diabetes (22.17% vs. 13.04%), hyperlipidemia (40.81%vs. 20.77%), and atrial fibrillation (42.99% vs. 10.14%). Mortality was significantly higher in the thrombectomy group (14.01% vs. 5.66%, p<0.001), with no difference in rates of good outcome. Following propensity matched analysis, there was no difference in mortality between the two groups, however there was a lower rate of good outcome in the thrombectomy group (35.03% vs. 49.24%, OR; [95% CI]: 0.56 [0.36–0.85], p<0.01). Patients were more likely to receive thrombectomy at urban teaching hospitals (OR; [95% CI]: 4.09 [1.44–14.3], p<0.01). Presence of ICH (OR; [95% CI]: 0.43 [0.18–0.99], p< 0.05), coma status (OR; [95% CI]: 0.24 [0.06–0.79], p<0.05) and hypertension (OR; [95% CI]: 0.21 [0.06–0.58], p< 0.001) were independent predictors of poor outcome among patients who had thrombectomy. Conclusion: In this nationally representative analysis, patients with CVST who underwent thrombectomy were younger, more likely to be women, and had more severe neurological disease. After adjusting for disease severity, there was no difference in the rate of in-hospital mortality between the patients who had thrombectomy and those medically managed. Presence of ICH, coma and hypertension were associated with poor outcome among patients who had thrombectomy. Further studies are warranted to explore appropriate patient selection for thrombectomy in CVST. Disclosures: T. Hardigan: None. N. Siddiqui: None. A. Hardigan: None. K. Yaeger: None. C. Kellner: None. R. de Leacy: None. J. Fifi: None. J. Mocco: None. S. Majidi: None.